Analyzing Facebook as a Promotional Tool for Umrah Services: A Study of PT. Jasiyah Travel Service Makassar - Rahmadia Aulia; Margaretha Wadid Rante; Wayan Suardana (Politeknik Pariwisata Makassar, 2024)
The demand for Umrah or Umrah worship by Muslims has increased, especially in Indonesia. Travel agencies are also increasing their promotional efforts to provide Umrah services. This research aims to 1) analyse the use of Facebook social media in promoting Umrah packages and 2) describe the constraints or obstacles in promoting Umrah packages by travel agencies. The research uses a qualitative approach to understanding travel agencies' use of social media. The research was carried out at PT. Jasiyah Travel Service, Makassar City, is one of the companies that provide Umrah services for Muslims in Indonesia—the research utilized interview data from company staff, especially those responsible for managing Facebook. The research results show that the company has utilised Facebook to promote Umrah packages. The company's target is adult and elderly customers, where there is a tendency to understand that adults and the elderly mostly use Facebook. The company admin staff has used Facebook to optimise its use as a promotional tool. Utilizing Facebook features are friends, pages, Facebook walls, captions, reels, stories, geotags or locations, likes, comments, messengers, and live broadcasts. However, the company still has features that need to be utilised properly. Company staff experienced problems utilising social media, namely, limited knowledge regarding Facebook's features and a need for updated information regarding the company's tourism products. This research proposes the importance of updating information based on new data, for example, company logos, Facebook, Instagram, website and email usernames. Detailed information about company products can be an effective promotional tool for reaching Umrah customers